2011
DOI: 10.3892/mmr.2011.708
|View full text |Cite
|
Sign up to set email alerts
|

Solitary huge hepatocellular carcinomas 10 cm or larger may be completely ablated by repeated radiofrequency ablation combined with chemoembolization: Initial experience with 9 patients

Abstract: Abstract. The treatment of solitary huge hepatocellular carcinoma (SHHCC) larger than 10 cm remains a challenge. The aim of the present study was to assess the therapeutic effects of repeated radiofrequency ablation (RFA) combined with chemoembolization on SHHCC. This was a retrospective study based on data obtained from a prospectively collected database that included 9 SHHCC patients who underwent repeated RFA combined with chemoembolization between July 2008 and June 2011. A new management strategy for SHHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In the past few years, we have observed a special subtype of HCC ≥10 cm, defined as SHHCC and exhibiting less metastatic capacity. 9 Yang et al 22 reported that the clinical and pathological characteristics and outcome after hepatic resection of some SHHCC cases are similar to those of small HCC, but significantly better than those of nodular HCC. However, the vast majority of such patients are not eligible for resection because of the severity of underlying cirrhosis when SHHCC is detected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the past few years, we have observed a special subtype of HCC ≥10 cm, defined as SHHCC and exhibiting less metastatic capacity. 9 Yang et al 22 reported that the clinical and pathological characteristics and outcome after hepatic resection of some SHHCC cases are similar to those of small HCC, but significantly better than those of nodular HCC. However, the vast majority of such patients are not eligible for resection because of the severity of underlying cirrhosis when SHHCC is detected.…”
Section: Discussionmentioning
confidence: 99%
“…In the TACE/TAE + RF ablation group, we used the procedures described previously. 9 Briefly, a primary central massive ablation was performed, followed by peripheral repeated RF ablations. In the new strategy group, a treatment strategy including sequential treatments was carried out in 3 phases.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations